Urgensi dan Korelasi Dakwah dalam Dunia Pendidikan - Mahfud, Mohammad Irsyad; Muhammad Fitrah Arifuddin; Muhammad Khoirul Rifai (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2024)
Da'wah and education have an important role in forming a quality society in terms of intelligence and spirituality. In an educational process there are efforts to change the behavior of students for the better, while da'wah has the aim of inviting humans to get happiness in the world and the hereafter. In this case there is a relationship between education and da'wah. This research includes a type of literature study research by looking for relevant theoretical references according to the case or problem found. With this article hopefully it can provide a little view of the relationship and importance of da'wah and education in everyday life, especially Islamic education.